Excess Liquidity and Effectiveness of Monetary Policy : Evidence from Sub-Saharan Africa - Saxegaard, Magnus (IMF Working Papers; Working Paper ;, 2006)
This paper examines the pattern of excess liquidity in sub-Saharan Africa and its consequences for the effectiveness of monetary policy. The paper argues that understanding the consequences of excess liquidity requires quantifying the extent to which commercial bank holdings of excess liquidity exceed levels required for precautionary purposes. It proposes a methodology for measuring this quantity and uses it to estimate a nonlinear structural VAR model for the CEMAC region, Nigeria and Uganda. The study suggests that excess liquidity weakens the monetary policy transmission mechanism and thus the ability of monetary authorities to influence demand conditions in the economy.